Phase relations in the ZrO2–La2O3–Gd2O3 system: Experimental studies and phase modeling. Issue 12 (12th June 2019) - Stopyra, Michał; Saenko, Ivan; Ilatovskaia, Mariia; Savinykh, Galina; Fabrichnaya, Olga
Abstract: The phase relations in the ZrO2 –La2 O3 –Gd2 O3 ternary system were experimentally studied and thermodynamic modeling was performed. Selected compositions were synthesized using the co‐precipitation method, equilibrated at 1673 and 1873 K, and analyzed using X‐ray diffraction (XRD) and scanning electron microscopy (SEM/EDX). The phase transformations were investigated using differential thermal analysis (DTA), and the heat capacities of (La1 − x Gd x )2 Zr2 O7 ( x = 0.25, 0.50, 0.75) compounds were measured using differential scanning calorimetry (DSC). Experimental studies showed a substantial extension of the fluorite phase into the ternary system and solid‐state transformations involving phases A (hexagonal), fluorite, B (monoclinic), and pyrochlore at 1845 K (DTA). Additionally, thermodynamic modeling was performed using the CALPHAD (CALculation of PHAse Diagrams) approach. Comparing the new experimental data and the calculations based on ternary extrapolations of the binary systems revealed major inconsistencies. One source of inconsistencies was related to the calculated phase equilibria in the binary La2 O3 –Gd2 O3 system. Additional experimental investigation of the binary system indicated an underestimated solubility of La2 O3 in the B phase in the temperature range 1673‐1873 K. Based on these new data, the mixing parameters of the B phase were re‐assessed. The new experimental results for the ternary system were used to optimize the mixing parameters of the fluorite, B and C (cubic) phases. All new experimental data were well reproduced by the improved thermodynamic description of the ternary system.